Generalized dispersion analysis of crystals with unknown symmetry and orientation - Hoefer, Sonja; Popp, Juergen; Mayerhoefer, Thomas G. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2018)
With generalized dispersion analysis it is possible to gain the dispersion parameters and dielectric tensor function of crystals with not only unknown orientation of the symmetry elements in within the sample but with also unknown crystal symmetry. The developed procedure is applied to two spectra sets of each crystal symmetry type to cover various levels of difficulty in the evaluation with generalized dispersion analysis.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Crystal orientation; Crystal symmetry; Dispersion analysis